2014
DOI: 10.1007/s12325-014-0117-9
|View full text |Cite
|
Sign up to set email alerts
|

Open-Label Study Assessing the Long-term Efficacy and Safety of Triple Olmesartan/Amlodipine/Hydrochlorothiazide Combination Therapy for Hypertension

Abstract: In patients with Grade 2-3 hypertension, long-term treatment with OLM/AML/HCTZ triple combination therapy was well tolerated and effective. A high level of BP control and a substantial reduction in the level of hypertension severity were achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 32 publications
4
14
0
Order By: Relevance
“…This extension, designed to reflect general clinical practice, showed that BP reductions were maintained over the long-term and associated with a high BP control rate (78.1%). 15 The present results add to these findings by demonstrating that adding HCTZ can increase BP-lowering in patients with inadequate BP control on a dual combination.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…This extension, designed to reflect general clinical practice, showed that BP reductions were maintained over the long-term and associated with a high BP control rate (78.1%). 15 The present results add to these findings by demonstrating that adding HCTZ can increase BP-lowering in patients with inadequate BP control on a dual combination.…”
Section: Discussionsupporting
confidence: 71%
“…After completing the double‐blind study described by Volpe and colleagues, patients entered a long‐term open‐label extension in which they were treated, according to investigators' preferences, with the aim of maintaining BP control. This extension, designed to reflect general clinical practice, showed that BP reductions were maintained over the long‐term and associated with a high BP control rate (78.1%) . The present results add to these findings by demonstrating that adding HCTZ can increase BP‐lowering in patients with inadequate BP control on a dual combination.…”
Section: Discussionsupporting
confidence: 64%
“…The rate of ADRs in the present study was low, with the most frequent ADRs being peripheral edema, dizziness, and hypotension, which is consistent with the safety profile of the three-drug combination in clinical trials. 14 , 16 , 17 In the TRINITY clinical trial, in which all patients received 12 weeks’ treatment with the highest dose level of each drug (40/10/25 mg), dizziness and peripheral edema were the most common ADRs, followed by headache and fatigue. 14 Similarly, in the 4-week study of the FDC tablet, the most prevalent treatment-emergent adverse events were peripheral edema and dizziness.…”
Section: Discussionmentioning
confidence: 99%
“… 16 With regard to effectiveness, attainment of a BP goal of <140/90 mmHg was experienced by 67% of patients in the present study, 70% in the TRINITY clinical trial, 14 and 78% in a 36-week open-label extension study that assessed the three-drug separate-tablet combination of olmesartan, amlodipine, and HCT. 17 Of note, subanalyses of the TRINITY trial revealed that the rate of BP goal attainment was lower among patients with diabetes mellitus (41.1%) or chronic cardiovascular disease (38.9%). 15 Given that the proportion of patients with diabetes mellitus was approximately twofold higher in the present study, this may have contributed to the slightly lower rate of BP goal attainment.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 2,543 patients who completed the double-blind phase, 2,540 patients initially underwent 8 weeks of single-blind treatment with OLM/AML/HCTZ (20 mg/5 mg/12.5 mg), after which 2,509 were entered into an open-label treatment phase. Of these, 2,439 patients (97.2%) completed the study [ 11 ].…”
Section: Introductionmentioning
confidence: 99%